Starting from scratch the life-changing lessons of Aeneas - Marcolongo, Andrea 1987- (Europa Editions, 2022)
"A meditation on rebuilding, recovery, and renewal that is also a fascinating portrait of antiquity's most complex and surprisingly modern hero. In times of peace and prosperity, one can turn to Homer to learn valuable life lessons, to experience the thrills and terrors of war, and to read about hair-raising adventures in distant lands. But when things do not go as planned, when we unexpectedly find ourselves at the center of an epoch-defining upheaval, then, writes Andrea Marcolongo, we must look to Virgil's Aeneas for an example of adaptability and resilience. In Marcolongo's fresh, nuanced portrayal, Virgil's Aeneas emerges as a multiform, deeply human hero, striking in his vulnerability and capacity for empathy. His journey of rebirth and rebuilding, from the ruins of Troy to the shores of Italy, teaches us that when all seems lost, with hope, perseverance, and a little bit of luck, we can seek and find new beginnings."--Publisher
Original title: La lezione di Enea
Keywords: Äneas; Vergilius Maro, Publius -- v70-v19 -- Aeneis; Aeneas / (Legendary character); Virgil / Aeneis; Epic poetry, Latin / History and criticism; Aeneis (Virgil); Epic poetry, Latin; Criticism, interpretation, etc